Midodareni in Javanese Wedding Ceremony on Communicating the Sustainability of Traditional Legacy Amongst Family - Wahyuningtyas, Bhernadetta Pravita (Jurnal Ilmiah Widya Sosiopolitika; Vol 6 No 1 (2024): ISU-ISU PEMBANGUNANDO - 10.24843/JIWSP.2024.v06.i01.p05, 2024)
This research was intended to gives a deep about the communicating sustainability from Midodareni event. Traditional rituals help people to deeply understand and respect further over the symbolic or non-verbal communication that used amongst them. Traditional wedding rituals increasingly unpopular over generation whilst actually live and remain amongst the society and becoming valuable cultural experience for the people. This research would like to describe the way cultural values and the legacy of traditional wedding rituals has been socialized, and perpetuated through communication in Indonesia especially on Javanese people. The constructivist paradigm was carried out to describes the phenomenon on the Javanese people’s cultural experience in absorbing the traditional rituals as the legacy amongst their family. The qualitative methods were used to collect data by observation and interviews face to face. This study found out that during communicating the traditional rituals, the cultural experience taught the Javanese younger generation more than just values and conventions but it also showed about moral virtues, generosity, hospitality, love, respect, and the soul of the tradition itself.